SUFISM AND ISLAMIC HERITAGE IN CENTRAL ASIA (The Journal of Interdisciplinary Human Studies, 2026)
Central Asia, with its rich historical and cultural heritage, has long been a significant center of Islamic intellectual and spiritual life. This region has produced numerous prominent scholars, theologians, jurists, and Sufi masters whose contributions have profoundly influenced the development of Islamic thought. The study of Sufi traditions, including major orders such as the Naqshbandiyya, Kubrawiyya, Yasawiyya, and Qalandariyya, provides insight into the historical, philosophical, and educational aspects of Islamic civilization in Central Asia. This research examines the origins, teachings, practices, and social functions of these Sufi orders, as well as their influence on moral values, education, and cultural development. Recent scholarly work in Uzbekistan highlights the role of classical Sufi texts, the systematization of mystical knowledge, and the significance of pilgrimage sites in fostering spiritual and intellectual growth. By analyzing both primary sources and contemporary studies, this article aims to present a comprehensive overview of Sufism’s historical legacy and its continuing relevance in modern Central Asian society.
Keywords: Sufism; Naqshbandiyya; Kubrawiyya; Yasawiyya; Qalandariyya; Islamic Studies; Central Asia; Islamic Civilization; Mysticism; Religious Education